A Review on Heavy Metals Effects on Soil, Plants, Human Health on Agricultural Micro-Organisms: The Impact of Heavy Metal-Containing Fertilizer on Soil, Plants, Human Health, and Aquatic Life (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Heavy metals are harmful to soil, plants, aquatic life and human health if their fixation is high in the fertilizer. Heavy metals show harmful impacts towards soil biota by influencing key microbial procedures and abatement the number and action of soil microorganisms. Indeed, even low centralization of heavy metals may repress the physiological digestion of plant. Taking up heavy metals from plants and then storing them along the natural lifestyle is a potential risk to animal and human health. Contaminants in aquatic frameworks, including heavy metals, invigorate the creation of receptive oxygen species (ROS) that can harm angles and other aquatic life forms. Henceforth the fertilizer must be use for horticulture it ought to be liberated from heavy metals. Along these lines, the present examination assessed the impacts of heavy metal containing manure on soil, plants, human health and aquatic life.